Identification of a FVa Binding Site on Prothrombin - Friedmann, Alexander (My University, 2017)
Thrombin is generated by the prothrombinase complex consisting of the enzyme factor (F) Xa, cofactor FVa, a negatively charged lipid surface and calcium ions. While FXa alone generates thrombin, the reaction rate increases by 5 orders of magnitude upon formation of prothrombinase. Previous work indicated that the kringle 2 domain of prothrombin is involved in binding FVa. Based on unpublished data that identified seven potential residues of the kringle 2 domain as the binding site for FVa (S160, Q177, Q179, R181, L182, V184 and T185), a variant with the latter six residues simultaneously mutated was generated (Q177A, Q179A, R181A, L182T, V184T, and T185A; PT6). Activation kinetics and thrombin generation of PT6 were compared with wild-type prothrombin (WTPT). Prothrombin activation along with DAPA showed a significant decrease in catalytic efficiency both in the presence and absence of FVa, but not without the membrane surface. Thrombin-activated platelets were found to have a similar effect to synthetic membrane for overall catalytic efficiency. SDS-PAGE analyses revealed a 40% decrease in meizothrombin potential compared with the wild-type, suggesting a decrease in a FVa-specific prothrombin activation by cleavage at Arg320. In the absence of FVa, initial rates of WTPT and PT6 consumption were similar while the overall thrombin generation was 48% lower with PT6, suggesting that the initial cleavage at Arg271 was unaltered while the secondary cleavage at Arg320 was reduced. Total thrombin generation was significantly decreased in PT6 compared with WTPT in a FVa-dependent manner, which is in contrast with the activation kinetics data. This suggests that simplified initial rate analyses may be insufficient in investigating a complicated multi-component enzyme such as prothrombinase. Taken together, the six residues of kringle 2 domain are important for efficient cleavage at Arg320 both in a FVa-dependent and FVa-independent manner.